2017
DOI: 10.1186/s12889-017-4350-4
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use and sexual risk behaviour among men and women in inner-city Johannesburg, South Africa

Abstract: BackgroundAlcohol misuse is a key factor underlying the remarkable vulnerability to HIV infection among men and women in sub-Saharan Africa, especially within urban settings. Its effects, however, vary by type of drinking, population group and are modified by socio-cultural co-factors.MethodsWe interviewed a random sample of 1465 men living in single-sex hostels and 1008 women in adjacent informal settlements in inner-city, Johannesburg, South Africa. Being drunk in the past week was used as an indicator of he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
40
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 59 publications
7
40
0
1
Order By: Relevance
“…Our findings reinforces results from previous studies [1, 3, 6, 8, 12] that alcohol is a potential risk factor for HIV and will stimulate scholarly debate and support the need for further research to establish whether a causal relationship exists between alcohol consumption and HIV status. Such empirical studies will contribute towards understand of structural drivers of HIV and the development of comprehensive evidence-based policies and population-specific HIV prevention interventions.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our findings reinforces results from previous studies [1, 3, 6, 8, 12] that alcohol is a potential risk factor for HIV and will stimulate scholarly debate and support the need for further research to establish whether a causal relationship exists between alcohol consumption and HIV status. Such empirical studies will contribute towards understand of structural drivers of HIV and the development of comprehensive evidence-based policies and population-specific HIV prevention interventions.…”
Section: Discussionsupporting
confidence: 89%
“…This attests to earlier observations [4, 8, 11] that alcohol consumption may increase risk-taking behaviors among individuals who may not have taken the same risk when they are sober, which potentially exposes them to HIV infection. For example, sex under the influence of alcohol was associated with a greater likelihood for paying for sex, use of physical force to have sex [12] and unprotected sex [11]. Alcohol consumption has also been suggested to increase the risk of becoming infected with HIV through its suppressive effects on the immune system [3].…”
Section: Discussionmentioning
confidence: 99%
“…There is a large body of evidence [25] to support the effectiveness of screening, brief interventions and referral to treatment (SBIRT) for alcohol-related problems, with these interventions being suitable for a range of settings such as emergency room settings, [26] workplace settings [27] and primary healthcare settings. [28] In keeping with previous findings, [16,29] our results suggest that being male and being a student were associated with the onset of alcohol use. This is of concern, since a systematic review conducted in 2016 confirms that hazardous alcohol consumption continues to be the most prevalent public health issue encountered by university students.…”
Section: Researchsupporting
confidence: 91%
“…This finding is consistent with a previous study in Cambodia which reported that FBWs consume alcohol and some engaged in transactional sex [ 19 ]. Among women in the general population, similar findings in South Africa [ 37 , 38 ] and Uganda [ 39 ] also reported that heavy alcohol consumption was associated with transactional sex. The above finding supports available evidence that alcohol consumption is associated with a number of risky sexual behaviours including transactional sex[ 25 , 28 ], unprotected sex and inconsistent condom use [ 40 , 41 ].…”
Section: Discussionsupporting
confidence: 54%